FLORA AND FAUNA OF KARSTIC CAVES OF ARMENIA AND NAGORNO KARABACH (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
17 karstic caves of Armenia and 8 caves of Nagorno Karabach are investigated. Brief representation of design of caves, history of their formation and also their biodiversity, in particular structure of their flora and fauna is given.
Keywords: flora and fauna; history of formation; biodiversity